Evaluation of Antibacterial Activity in Nanoparticles Ointment Preparation using Ethanol Extract of Miana Leaves (Coleus Atropurpureus (L.) Benth) - Tria Prayoga (Nanomedicine Research Journal, 2019)
Objective(s): Compared the nanoparticles form of Miana leaves with its extracts, even in single state or ointment preparation. Hence, SPSS program using Paired T Test is obtained to know the differences between them. Method: The method used in this research is experiment in which try to change the extract form to be nanoparticles and be compared. The mixture of Poly Acrylic Acid (PAA) and calcium chloride using ionic glass method could change the size of Miana leaves’ ethanol extract to be nanoparticle with the average diameter amounted 89,77 nm. The equality showed that 2,50% of Miana leaves is equal with 1,17% of nanoparticles Miana leaves extract. Results: The result then revealed that ethanol extract of Miana leaves had antibacterial activities toward Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa. The nanoparticles form proven can improve the stability and medicine’s administration. In the medicine administration system, nanoparticles has function as carrier by dissolving, trap, encapsulate, and attached the medicine in the matrix. Then, by mixed poly acrylic acid and calcium chloride using ionic glass method, the nanoparticles would be formed. Conclusion: This research indicated that Miana leaves extract of nanoparticles ointment is safe and did not irritate the skin.